Effect of Video-Based versus Personalized Instruction on Errors during Elastic Tubing Exercises for Musculoskeletal Pain: A Randomized Controlled Trial. (10th March 2014) - Jay, Kenneth; schraefel, m. c.; Brandt, Mikkel; Andersen, Lars L.
Abstract : Workplace interventions have shown beneficial results of resistance training for chronic pain in the neck, shoulder, and arm. However, studies have relied on experienced exercise instructors, which may not be an available resource at most workplaces. The objective of this study is to evaluate the technical performance level of upper limb rehabilitation exercises following video-based versus personalized exercise instruction. We recruited 38 laboratory technicians and office workers with neck/shoulder pain for a two-week exercise training period receiving either (1) personal and video or (2) video only instruction in four typical neck/shoulder/arm rehabilitation exercises using elastic tubing. At a 2-week follow-up, the participants' technical execution was assessed by two blinded physical therapists using a reliable error assessment tool. The error assessment was based on ordinal deviation of joint position from the ideal position of the shoulder, elbow, and wrist in a single plane by visual observation. Of the four exercises only unilateral shoulder external rotation had a higher normalized error score in the V group of 22.19 (9.30) to 12.64 (6.94) in the P group (P = 0.002 ). For the remaining three exercises the normalized error score did not differ. In conclusion, when instructing simple exercises to reduce musculoskeletal pain the use of video material is a cost-effective solution that can be implemented easily in corporations with challenging work schedules not allowing for a fixed time of day to go see a personal trainer.